Pengaruh Penerapan Sistem E-Filing, Aksesibilitas Sistem Pajak Digital, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Pamekasan - Amilia, Febriana Rosa; Hakim, Lukmanul (SAFE-Network, 2025)
This study analyzes the influence of the e-filing system implementation, digital tax system accessibility, and tax sanctions on Individual Taxpayer Compliance at KPP Pratama Pamekasan. The research background is grounded in the significant decline in taxpayer compliance in Pamekasan over the past two years, despite the national trend of increasing tax revenue. The study aims to determine how tax administration modernization through e-filing, the ease of accessing digital tax services, and the enforcement of tax sanctions influence taxpayer compliance behavior. A quantitative research approach using a survey method was employed, with primary data collected from 420 Individual Taxpayers registered at KPP Pratama Pamekasan. The data were analyzed using multiple linear regression to examine the effect of each independent variable. The results indicate that the implementation of the e-filing system has a positive and significant effect on taxpayer compliance, suggesting that better e-filing implementation leads to higher compliance in annual tax reporting. Digital tax system accessibility also shows a positive and significant effect, indicating that ease of access to digital services encourages higher compliance. Furthermore, tax sanctions have a positive and significant impact in line with deterrence theory, where the presence of strict sanctions increases compliance. In conclusion, these three variables simultaneously contribute to improving individual taxpayer compliance in Pamekasan. The findings provide valuable insights for tax authorities to enhance digital service quality and strengthen tax law enforcement mechanisms.